2022
DOI: 10.1111/jjns.12472
|View full text |Cite
|
Sign up to set email alerts
|

Measurement tools that assess the quality of transitional care from patients' perspective: A literature review

Abstract: Aim: Transitional care is important for improving the quality of life of patients discharged from hospitals. Patient-reported experience measures help improve transitional care quality. Thus, this literature review aimed to identify and appraise measurement tools that assess transitional care quality from the patient's perspective and identify its components. Methods: Development and validation studies were systematically searched in the PubMed and CINAHL databases. The review team appraised the methodological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Its purpose is to serve as an indicator of transitional care quality by assessing the patients’ experience of the transition process [ 18 ]. PACT-M covers both the immediate post-discharge period and the longer-term experience of managing health and care at home by examining the patients’ experience at two points of time; one week after discharge (using PACT-M1) and one month after discharge (using PACT-M2) [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its purpose is to serve as an indicator of transitional care quality by assessing the patients’ experience of the transition process [ 18 ]. PACT-M covers both the immediate post-discharge period and the longer-term experience of managing health and care at home by examining the patients’ experience at two points of time; one week after discharge (using PACT-M1) and one month after discharge (using PACT-M2) [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a systematic review, seven measurement tools that assess transitional care quality from the patient’s perspective have been identified and appraised [ 15 ]. Among these, Care Transitions Measure-15 (CTM-15) and PACT-M are the most comprehensive in covering the transition of care process [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, we developed the conceptual framework to measure patients' readiness for hospital discharge through a systematic review of patient‐reported scales of transitional care and reports of patients with heart failure (Yoshimura & Sumi, 2022a, 2022b). We reviewed 47 reports and seven different existing measures; then, we developed an initial item pool with a conceptual framework of six categories to assess patients' readiness for hospital discharge.…”
Section: Methodsmentioning
confidence: 99%
“…In studies overseas, in addition to using readmission rate as an indicator of TCS, emergency department (ED) visits, mortality rate, and quality of life have been used as evaluation indicators for discharged patient management projects. 13 14 15 Furthermore, in some cases, “providing education and counseling for patients during hospitalization,” which may affect patient skills for post-discharge self-management, is included as an indicator. 13 16 In contrast, in the case of a pilot project titled Support of Post-discharge Management and Connection to Community Resources for Patients with Acute Conditions, which was implemented in Korea in 2020, only pre- and post-discharge patient satisfaction and participation were used as indicators; thus, there is a clear need for the development of more comprehensive evaluation indicators.…”
Section: Introductionmentioning
confidence: 99%